Identification of Coronaviruses, Paramyxoviruses, Reoviruses, and Rotaviruses among Bats in Nigeria - Kia, Grace S. N.; Tao, Ying; Umoh, Jarlath U. (The American Society of Tropical Medicine and Hygiene, 2021)
Bats are often consumed by some ethnic groups in Nigeria despite association of bats with many important emerging viruses. More than 300 bats representing eight species were captured during 2010–2011 in eight locations of northern Nigeria. Available fecal swabs (n = 95) were screened for the presence of arenaviruses, CoVs, paramyxoviruses (PMVs), reoviruses, rhabdoviruses, and influenza viruses using generic reverse transcription–polymerase chain reaction assays. Here, we document the detection of CoVs, PMVs, reoviruses, and rotaviruses (RVs) in Nigerian bats. The Nigerian bat CoVs are grouped within other bat SARS-CoV–like viruses identified from Ghana in a sister clade next to the human SARS-CoV clade. The phylogenetic analysis indicated a broad range of RVs present in Nigerian bats, some cluster with human RVs and some represent novel species. Our study adds that continuing global surveillance for viruses in bats to understand their origin, adaptation, and evolution is important to prevent and control future zoonotic disease outbreaks
Keywords: Jacob K. P. Kwaga; Suxiang Tong; Bats; Nigeria; Coronaviruses; Paramyxoviruses; Ahmadu Bello University; ACENTDFB